Publication Trends of Research on Polypoidal Choroidal Vasculopathy During 2001–2020: A 20-Year Bibliometric Study - Wang, Yimin; Xie, Minyue; Zhang, Min; Zhao, Xiaohuan; Zhu, Xinyue; Wang, Yuwei; Chen, Yuhong; Chen, Jieqiong; Sun, Xiaodong (Frontiers in Medicine, 2022)
Introduction: Polypoidal choroidal vasculopathy (PCV) is a special subtype of AMD, which is one of the leading threats to vision health worldwide. At this time, many aspects of PCV, from how it works to potential treatments, remain a mystery. In this study, we explored the frontier researches and revealed the study trends within the study of PCV. Methods: We collected all the publications in this field from 2001 to 2020, analyzed trends within them, and defined the contributions of various countries/regions, institutions, authors, and journals. Additionally, VOSviewer software was used to define the hot keywords in this field. Results: A total of 1190 publications were ultimately examined; We found that PCV is becoming an increasingly relevant topic of research, and that Japan has contributed the most publications (428), the most citations (14504 in total), and the highest H-index value (62) to the field. Our keywords analysis was classified into four clusters to show the hotspots within the study of PCV, namely mechanism-related, imaging-related, prognosis-related, and therapy-related topics. The average years in which the keywords appeared the most were also calculated, and we identified anti-VEGF therapy, anti-complement therapy and angiography as having been the main focus in recent years. Conclusions: These results helped clarify the comprehensive research progress that has been made as well as the future trends in the study of PCV, which can assist and guide future research.